2017
DOI: 10.1093/aob/mcx188
|View full text |Cite
|
Sign up to set email alerts
|

Critical temperature and precipitation thresholds for the onset of xylogenesis of Juniperus przewalskii in a semi-arid area of the north-eastern Tibetan Plateau

Abstract: Xylogenesis in semi-arid regions with dry winters and springs can start when both critical temperature and precipitation thresholds are reached. Such findings contribute to our knowledge of the environmental drivers of growth resumption that previously had been investigated largely in cold regions without water shortages during early growing seasons. Models of the onset of xylogenesis should include water availability to improve predictions of xylem phenology in dry areas. A mismatch between the thresholds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 55 publications
2
55
1
Order By: Relevance
“…, Ren et al. ). In addition, drought has also increased the frequency of missing rings in alpine birch forests in the central Himalayas (Liang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Ren et al. ). In addition, drought has also increased the frequency of missing rings in alpine birch forests in the central Himalayas (Liang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies showed that interactions between temperature and precipitation leading to dry conditions limit seedling establishment and tree species distribution shifts in the Rocky Mountains (Hessl and Baker 1997, Lloyd and Graumlich 1997, Elliott 2012, Moyes et al 2015, Kueppers et al 2017. High-elevation forests on the dry northeastern Tibetan Plateau are increasingly at risk of growth decline and mortality , Fang et al 2018, Ren et al 2018. In addition, drought has also increased the frequency of missing rings in alpine birch forests in the central Himalayas (Liang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Under severe drought conditions, high competition for moisture between neighboring trees will further exacerbate drought stress for tree growth [47][48][49][50]. As shown in a recent study, low winter and spring precipitation can cause a delay of the initiation of xylogenesis and contribute to the occurrence of the locally missing rings in years with extremely dry springs [51]. Ongoing warming temperatures could not only cause soil moisture deficiency but also amplify temperature-induced drought stress, thereby limiting tree growth and posing a risk of die-off under a warming climate [52][53][54][55][56].…”
Section: Climate-and Drought-growth Associations: the Pivotal Role Ofmentioning
confidence: 93%
“…It has been shown before that in a dry environment, the onset of xylogenesis is regulated by both the temperature threshold and moisture supply [64]. Later, both the growth rate during the season and the timing of the growth cessation are regulated by water deficit [65].…”
Section: Climatic Response and Growth Modeling Of Treesmentioning
confidence: 99%